Green intellectual capital and competitive advantage: the moderating role of corporate philanthropy during COVID-19 - Naseem, Muhammad Akram; Battisti, Enrico; Salvi, Antonio; Ahmad, Muhammad Ishfaq (Journal of intellectual capital, 2024)
PurposeThis study examines the relationship between green intellectual capital (GIC) and competitive advantage (CA) and proposes the moderating role of corporate philanthropy types (cash, in-kind and both) during the COVID-19 pandemic. In particular, this study investigates the types of corporate philanthropy, strengthening the link between GIC and CA for Chinese listed firms during a pandemic.Design/methodology/approachCross-sectional data were collected from 248 chief executive officers (CEOs) of Chinese firms listed on the Shanghai Stock Exchange through a structured questionnaire. Regression analysis was employed to test the proposed hypotheses.FindingsThe findings reveal that all types of GIC positively influence a firm's CA. Furthermore, all three types of philanthropy – cash, in-kind and both – moderate the relationship between GIC and CA. However, the intensity of moderation was higher in the case of in-kind philanthropy than in the other two types.Originality/valueTo the best of the authors' knowledge, this is the first empirical study to examine the relationship between GIC (considering its three components: human, structural and relational capital) and CA in China. The study finds different types of philanthropy as moderating variables to better explain the relationship between GIC and CA. Further, it contributes to a new line of research that aims to study philanthropic aspects connected to the GIC debate.